Evaluation of the effect of mouthwashes on titanium alloy miniscrews: a systematic review - Es-Samti, Lamiae; Oliveira, Ana Catarina; Santos, Sofia; Santos, Catarina; Sousa-Santos, Primavera (Scientific Letters, 2024)
Orthodontic miniscrews (MSs) are increasingly used in orthodontics, providing good treatment results, particularly Ti-6Al-4V MSs. Sometimes, after placing the MSs, orthodontists prescribe mouthwashing to avoid risk of infection, thus ensuring good stability and optimizing the final treatment result. The aim of this review is to analyze the effects of chlorhexidine (CHX) and sodium fluoride (NaF) mouthwashes on the surface of titanium alloy MSs and to analyze the cytotoxicity, corrosion and ion release caused. The search was carried out in the PubMed, ScienceDirect and Google Scholar databases for articles published between January 2011 and December 2023. For the study, ten articles were selected, based on exclusion and inclusion criteria. Numerous studies show that NaF seems to have more negative effects than CHX, in terms of the quantity of ions released and in terms of alteration of the surface layer, with greater corrosion and destruction of the surface microstructure. In conclusion, mouthwash with NaF alters the surface layer, causing corrosion and release of ions. Mouthwash with CHX gives good results because it causes minimal alteration of the surface layer of the MSs and minimal release of contained ions.